Ricardo Palma, maker of traditions. A review by Chilean critic Ernesto Montenegro (1924) - Arrizabalaga Lizarraga, Carlos (2020)
The article presents a news about a Chilean literary critic and a review published in the New York Times in 1924 about the book Mis últimas tradiciones y Cachivachería by Ricardo Palma, published in Barcelona in 1906. Ernesto Montenegro stood out as a diffuser of North American literature in the great American metropolis, but in this particular situation, there are some contradictions between the sincere recognition of the author’s merits and the negative judgment that the traditionist’s work receives.